Pregnancy With Multidrug-Resistant Pulmonary Tuberculosis and Autoimmune Hemolytic Anemia Complicated by Intrauterine Growth Restriction - A Case Report - Putri Indah Permata; Renny Aditya; Ruth Widhiati Raharjo Putri; Mohamad Isa; Sigit Prasetia Kurniawan; Ira Nurrasyidah (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2025)
AbstractIntroductionIntrauterine growth restriction (IUGR) is a major obstetric complication often caused by maternal infections and anemia. We present a case of IUGR in a pregnant woman caused by multidrug-resistant tuberculosis (MDR-TB) and autoimmune hemolytic anemia (AIHA).Case presentationA 37-year-old G5P2A2 woman with confirmed MDR-TB and AIHA was treated with levofloxacin, clofazimine, cycloserine, ethambutol, bedaquiline, and methylprednisolone. Fetal biometry showed estimated fetal weight below the 10th percentile, with a significantly declining growth curve thereafter. After administration of fetal lung maturation at 33 – 34 weeks, she underwent an elective cesarean section at 35 – 36 weeks. A female infant weighing 1,840g was delivered. The treatment for MDR-TB and AIHA in the mother was continued afterward.ConclusionPregnancies complicated by MDR-TB and AIHA require strict monitoring and individualized multidisciplinary treatment. Further research is needed to establish treatment strategies that improve maternal and fetal outcomes in similar cases.Keywords : Autoimmune hemolytic anemia; intrauterine growth restriction; multidrug resistance; pregnancy; tuberculosis. Kehamilan dengan Tuberkulosis Paru Resisten Obat Ganda dan Anemia Hemolitik Autoimun yang Diperberat oleh Pertumbuhan Janin Terhambat – Laporan Kasus AbstrakPendahuluanIUGR adalah komplikasi obstetrik yang dapat disebabkan infeksi dan anemia pada maternal. Pada kasus ini dipresentasikan kasus wanita hamil dengan IUGR yang disebabkan multidrug resistant TB (MDR-TB) dan autoimmune hemolytic anemia (AIHA).Ilustrasi kasusIbu hamil 37 tahun G5P2A2 datang dengan TB-MDR dan AIHA. Pasien menjalani terapi TB-MDR dengan levofloksasin, klofazimin, sikloserin, etambutol, dan bedaquiline, serta metilprednisolon untuk AIHA. Pada fetal biometri ditemukan estimated fetal weight (EFW) di bawah 10 persentil dengan kurva pertumbuhan janin menurun signifikan setelahnya. Setelah dilakukan induksi pematangan paru janin pada usia kehamilan 33 - 34 minggu, operasi sesar elektif dilakukan pada usia kehamilan 35 – 36 minggu melahirkan bayi perempuan dengan berat janin 1840gram. Pengobatan TB-MDR dan AIHA pada ibu dilanjutkan setelahnya.KesimpulanKehamilan dengan TB dan AIHA memerlukan pemantauan ketat dan terapi multidisiplin yang terindividualisasi. Penelitian lebih lanjut diperlukan.Kata kunci : Hemolitik anemia autoimun; kehamilan; pertumbuhan janin terhambat; resisten obat; tuberkulosis.